2014
DOI: 10.1161/hypertensionaha.113.02526
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Mammalian Target of Rapamycin With Rapamycin Reverses Hypertrophic Cardiomyopathy in Mice With Cardiomyocyte-Specific Knockout of PTEN

Abstract: The online-only Data Supplement is available with this article at http://hyper.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…Using a pressure overload murine model, Nakai et al (2007) suppressed autophagy 1 week after transverse aortic constriction (TAC) operation. More recent reports also revealed diminished cardiac autophagy or autophagy flux en route to the compromised cardiac function in the face of pressure overload (Marino et al, 2014;Shen et al, 2015;Won Suk Jahng et al, 2015;Xu et al, 2014). Furthermore, Pfeifer et al (1987) found that autophagic vacuoles were significantly decreased to 50% within a 10-min infusion of b-adrenergic agonist isoproterenol.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Using a pressure overload murine model, Nakai et al (2007) suppressed autophagy 1 week after transverse aortic constriction (TAC) operation. More recent reports also revealed diminished cardiac autophagy or autophagy flux en route to the compromised cardiac function in the face of pressure overload (Marino et al, 2014;Shen et al, 2015;Won Suk Jahng et al, 2015;Xu et al, 2014). Furthermore, Pfeifer et al (1987) found that autophagic vacuoles were significantly decreased to 50% within a 10-min infusion of b-adrenergic agonist isoproterenol.…”
Section: Discussionmentioning
confidence: 92%
“…Dysregulated autophagy has been demonstrated to contribute to the pathogenesis of atherosclerosis, ischemia/reperfusion injury, cardiomyopathy, diabetes mellitus, and hypertension (Ren and Taegtmeyer, 2015;Saito and Sadoshima, 2015). In addition, autophagy is known to participate in the pathogenesis of pressure overload-induced heart diseases (Martinet et al, 2007;Shen et al, 2015;Won Suk Jahng et al, 2015;Xu et al, 2014). Using a pressure overload murine model, Nakai et al (2007) suppressed autophagy 1 week after transverse aortic constriction (TAC) operation.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have suggested that autophagy is involved in the development of cardiomyocyte hypertrophy. 42,43 Several recent studies have shown that statins induced autophagy in mammalian cells, such as human rhabdomyosarcoma cells and PC3 cells. 44,45 More recently, simvastatin was demonstrated to increase autophagy in human airway smooth muscle cells and coronary arterial myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to preserving Serca2a activity and limiting ER stress, PERK may also exert cardiac protective effects through modulating additional molecular pathways implicated in CHF development. A recent study demonstrated that PERK activation can induce cardiomyocyte autophagy 34 , an evolutionary stress response that is important for adaptation to cardiac stress 35, 36 .…”
Section: Discussionmentioning
confidence: 99%